Implementasi Metode Analytical Hierarchy Process (AHP) Dalam Sistem Pendukung Keputusan Untuk Rekomendasi Biro Perjalanan Umrah Di Kota Jambi - Meisarah, Neisya; Fachruddin; Jasmir (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
The development of information technology has had a significant impact in various sectors, including the Umrah travel sector. The number of Umrah travel agencies in Jambi City makes it difficult for prospective pilgrims to make choices that suit their needs. Therefore, a Decision Support System (SPK) is needed that can assist in the process of selecting an Umrah travel agency objectively and systematically. This study aims to develop and implement a Decision Support System (DSS) in the selection of Umrah travel agencies in Jambi City using the Analytical Hierarchy Process (AHP) method. This system is designed to assist prospective pilgrims in choosing the appropriate Umrah travel agency based on the criteria of legality, facilities, trip duration, reputation, and additional services. The system was developed using the PHP programming language and MySQL database, with a system model designed using the Unified Modeling Language (UML) and the waterfall development method. The results showed that PT Al Mabrur Nadia Insani is the best Umrah travel agency based on Analytical Hierarchy Process (AHP) calculations, with the highest score of 0.412, so that the system developed is able to provide objective and systematic recommendations, assist prospective pilgrims in choosing the optimal Umrah travel agency, and provide insight for Umrah travel agencies to improve their services.